UFAD guide : design, construction, and operation of underfloor air distribution systems (ASHRAE, 2013)
"Guide provides assistance in the design of UFAD systems that are energy efficient, intelligently operated, and effective in their performance. It also describes important research results that support current thinking on UFAD design"-- Provided by publisher.
Keywords: Air conditioning.; Ventilation.; Air ducts.; Floors.; elektronické knihy; electronic books